Strategi Penguatan Fungsi Keimigrasian Melalui Sinergi Lintas Sektor: Analisis Penanganan Perlintasan Ilegal di Perbatasan Kalimantan Barat-Malaysia - Abhimanyu Araryaputra; Hanifa Maulidia; Mochammad Ryanindityo (MAN Insan Cendekia Jambi, 2025)
West Kalimantan Province, remain a significant challenge to the national immigration control system. This phenomenon consists of two main forms: first, the entry of foreign nationals without official documents and the irregular departure of Indonesian citizens, particularly prospective migrant workers, through non-procedural means. These crossings typically utilize unofficial routes or jalur tikus—paths that are difficult to access and poorly monitored. Such practices often involve third parties, including brokers, illegal agents, or transnational syndicates that facilitate the unlawful movement of people. In addressing this issue, the Directorate General of Immigration plays a strategic frontline role; however, implementation remains constrained by limited human resources, infrastructure deficiencies, and the suboptimal presence of authorized immigration officers at traditional border posts. This study employs a descriptive qualitative approach using literature review methods to analyze the forms of illegal crossings, institutional challenges faced by immigration authorities, and the importance of cross-sectoral collaboration in border surveillance. The findings reveal that joint operations involving multiple agencies have resulted in a 27% increase in the detection of illegal crossers within a six-month period compared to separate patrols. However, collaboration among agencies such as the military (TNI), police (POLRI), National Border Management Agency (BNPP), Migrant Worker Protection Agency (BP2MI), and local governments has not been fully effective due to weak coordination, the absence of an integrated monitoring system, and a lack of unified standard operating procedures (SOPs). Therefore, strengthening immigration functions requires institutional synergy, improved officer capacity, the use of modern surveillance technologies, and active community involvement through a sustainable and adaptive participatory monitoring framework tailored to border characteristics.